The relationship between gender perception levels and infertility distress of infertile women in a university hospital, Turkey. Issue 1 (15th December 2020) - Doğan Yüksekol, Özlem; Duman, Mesude; Durgun Ozan, Yeter
Abstract : Purpose: This study was conducted to analyze the correlation between gender perception and infertility distress of infertile women. Design/methodology/approach: This was a descriptive-analytical study conducted with 255 women receiving treatment in the in vitro fertilization unit of a medical faculty hospital in Turkey. Study data were collected using sociodemographic questions as well as the Perception of Gender Scale (PGS) and the Infertility Distress Scale (IDS). Findings: It was found that the PGS mean score was 69.65 and the IDS mean score was 53.1. It was determined that there was a negative, moderate and significant correlation between gender perception and infertility distress levels of women in the infertility treatment process ( r = −0.263, p < 0.001). Originality/value: As a result of the study, a negative, moderate, significant correlation was detected between gender perception and infertility distress.